PENGARUH LATIHAN BERLARI ZIG-ZAG MELEWATI CONE TERHADAP KELINCAHAN DRIBBLING SEKOLAH SEPAK BOLA WONER 2012 U-13 PEKANBARU - M. Febrizaldi, M. Febrizaldi; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstark: The problem in this research is that in dribbling, the movement of the feet that carry the ball is very slow and less agile, and athletes when dueling for the ball are often late and lose to their opponents. The form of this research is (one group pretest-postest design) with a population of U-13 2012 Woner SSB. The data in this research related to the entire population, namely 16 subjects. The instrument used in this research was the dribble test, which aims to determine the effect of zigzag walking training through the cone. Based on the analysis of the normality test on the independent variable (X), it produces a LoMax of 0.121 and an L table of 0.213, which means that LoMax <L table. while the dependent variable (Y) produces LoMax of 0.104 and Ltable of 0.213. This means that LoMax <L The data table is normally distributed. When testing the t-distribution of the hypothesis, it can be concluded that between the variable x and the variable y the value of t = 4,750 is obtained, then tcount> ttable (4,750)> (1,753), then Ha is accepted , in other words, there is a significant effect on the zigzagging through the cone against the dribbling dexterity of the Woner 2012 U-13 Pekanbaru football school.Key Words: Zigzag running training through the cone, Dribbling agility, Football